Instructional program for multigrade teachers at Cochea Arriba Elementary School, David Chiriquí 2010 - Gómez, Rony Steve; Saldaña Rivera, Isabel Cristina; Zapata Quintero, Tirza Mabel; Vargas, Victor; Quintero, Lourdes (David, Panamá : UDELAS, 2010)
The educatonal system in our territory does not promote properly the snowledge of the language. The results of english test at the University of Panama support this detail. As a result, our students graduate with low levels of english knowledge, or even without it. For those reasons, we created a practical guide to multigrade teachers and parents of Cochea Arriba Elementary School to facilitate teaching - learning english.
INDEX Quote Dedication Acknowledgments General index Introduction CHAPTER I. FRAME OF REFERENCE OF THE PROJECT CHAPTER II. EXPECTED DESCRIPTION OF THE PROPOSAL 2.1. Expected description of the proposal 2.1.1. Expected results of the project 2.2. Project's areas of action 2.2.1. Academic area 2.2.2. Scholar infraestructure area 2.2.3. Cultural development area 2.3. Action lines 2.4. Activities 2.4.1. Descriotion of activities 2.4.2. Methodology to implement the execution of activities 2.4.3. Guides for instrument use 2.5. Schedule of activities 2.6. Administrative structure 2.7. Budget 2.7.1. Human resources 2.7.2. Material resources 2.7.3. Finacial resources 2.8. Evaluation 2.8.1. Evaluation guide CHAPTER III. PRACTICAL GUIDE TO TEACHING ENGLISH LANGUAGE TO MULTIGRADE TEACHERS AT COCHEA ARRIBA ELEMENTARY SCHOOL Conclusions Recommendations Bibliography
Incluye Index
Documento presentado para optar por el título de Licenciatura en Docencia en Inglés
Incluye Bibliografía
No se presta a domicilio
No se saca fotocopia
Keywords: ENGLISH -- PROYECTO COMUNITARIO DE LICENCIATURA; SCHOOL OF EDUCATION; ENGLISH FACULTY; LICENCIATURA EN DOCENCIA EN INGLÉS; COCHEA ARRIBA ELEMENTARY SCHOOL - DAVID - CHIRIQUÍ